Awareness of workplace hazards and preventive measures among sandstone mineworkers in Rajasthan, India: A cross-sectional study - Absar Ahmad (Journal of Health and Social Sciences)
Objective: The aim of this study was to assess awareness of workplace hazards and personal protective equipments (PPEs) among mineworkers employed in a sandstone quarry in Rajasthan, India. Materials and Methods: A cross-sectional study of 218 miners was conducted in Karauli, Rajasthan, India. We used a standardized semi-structured questionnaire that was administered to each subject by face-to-face interviews. Descriptive statistics and Pearson chi-square test were used to show frequency distributions and associations between variables. Results: Almost all respondents were aware of at least one hazard in mining occupation (93.6%), but no of them was trained by a recent (within 1 year) health and safety training course. However, mineworkers recognized only the risk of injury (74.3%) and exposure to crystalline silica dust (40.4%). A high percentage of mineworkers were aware of PPEs (87.6%), but an only 16.5% of them used PPEs during their employment. The only PPEs mentioned by mineworkers was the dust protective mask. Occurrence of at least one occupational injury during work-life was associated with use of dust masks, while work-related diseases were associated with a low level of education, underweight (BMI < 18.5 kg/m2), and current smoking. Awareness of workplace hazards was associated with age less than 60, young age of starting work in mines (< 30 years), hours work per day (< 8 hr), and no availability of drinking water facility. Failure to use PPEs at work was statistically significant associated with belonging to scheduled castes or scheduled tribes, lower distance from home to workplace (1‒3 Km), hours work per day (< 8 hr), and no availability of safe drinking water. Discussion and Conclusion: In Rajasthan, India, there is a certain level of awareness about workplace hazards but usage of PPEs by sandstone mineworkers is very low. Policy makers should implement health and safety training programmes to promote use of PPEs among mine workers.